The Use of Crossword for Teaching English Vocabulary at ICC Ladang Kosma - Sukiyah Sukiyah; Rini Listyowati; Uni Adiroh (Action Research Journal Indonesia (ARJI), 2025)
This study investigated the use of crossword puzzles as a strategy to overcome challenges in English vocabulary acquisition, particularly those arising from the limitations of traditional learning methods such as memorization. This study aimed to analyze the effectiveness of crossword puzzles as a teaching method and explore students' perceptions of its use. Using a qualitative case study approach, six students at ICC Ladang Kosma Malaysia participated in this study. The subjects in this study were grade 6 students who were undergoing an English learning program. They were selected based on their active participation in the learning process and their willingness to engage in teaching activities using crossword puzzles. Data were collected through observation, semi-structured interviews, and documentation. Data were analyzed using an interactive model, which included three main stages: data reduction, data presentation, and conclusion drawing. The findings of this study revealed that the structured implementation steps of preparation, guided practice, and individual assignments effectively improved students' vocabulary mastery, with scores ranging from 80 to 100. Students highlighted that the activities were fun, interesting, and beneficial for memory retention. The contribution of this study lies in providing insights for educators to develop more interactive teaching methods that are in accordance with students' learning characteristics, so that the learning process becomes more effective and meaningful